(untitled) (Damascus University Journal of agriculture sciences, 2021)
A field experiment was made in Hout research station, general commotion of scientific agriculture research, 30 km southern of As-Suwaidaa, in 2015-2016 , where the soil is heavy clay, medium depth, poor organic matter poor calcium carbonate. Three experimental treatments were tested: (1) control treatment is mineral fertilization (O0), (2) 0.75% of soil wight organic fertilization with goats manure to 25 cm in depth (O1), (3) 1.5% of soil wight organic fertilization with goats manure to 25 cm in depth (O2), were tested to evaluate their effects on some soil physical properties such as bulk density, specific density, total porosity and air filed porosity, at field capacity. And their effects on some hydrological properties such as field capacity, permanent wilt point and total available water. A complete randomized design with three replications was used. Results showed that the increases of organic fertilization with goats manure caused a significant decrease in specific density, total porosity, air filed porosity at field capacity to(0.75%, 1,78%), (0.35%, 1.56%), (1.70%, 12.45%) in (O1), (O2) respectively compared with (O0). The addition of goats manure (O1), (O2) caused a significant increase in field capacity, permanent wilt point and total available water to (0.54%, 5.66%), (0.97, 2.50%), (0.14%, 8.21%) respectively compared with (O0) to 25 cm depth. this reflects the importance of organic fertilization with fermented goats wastes at 1.5% of soil wight to 25 cm in depth to improve its physical and hydrological properties